Generic Construction of Dual-Server Public Key Authenticated Encryption With Keyword Search - Keita Emura (IET Information Security)
In this paper, we propose a generic construction of dual-server public key authenticated encryption with keyword search (DS-PAEKS) from PAEKS, public key encryption, and signatures. We also show that previous DS-PAEKS scheme is vulnerable by providing a concrete attack. That is, the proposed generic construction yields the first DS-PAEKS schemes. Our attack with a slight modification works against previous dual-server public key encryption with keyword search (DS-PEKS) schemes.